(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The author analyses the relation between privacy and the powers to collect evidence in the digital environment. With the aim to identify main problems of police powers, the author analysed the Supreme Court, ECHR and ECJ case-law on degrees of intrusion. The lowest degree refers to the collection of general data that does not include collection of the content of communications. According to the results of the research, such a degree of intrusion in Croatian case-law is not considered to be a serious one. For these powers, the retention of data is necessary, and according to the ECJ and ECHR decisions, it must be appropriately regulated. More stringent measures imply surveillance of communications content. The research results show that such measures are prescribed with considerably stricter standards. In addition, information that are available on social networks or similar sources may also be used in criminal investigation. The concept of total internet memory includes both positive and negative events, producing digital image of users. The development of new rights in this area, just as in the aforementioned, shows that the new standards are necessary in the digital domain.